Penanaman Toleransi Beragama pada Anak Melalui Pendidikan - Nurhattati Fuad (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT: As the plural nation, the peace culture is something necessary to develop and to build for the sake of building local, national, regional, and global security. For this purpose, whatever religious tolerance programs are important, urgent, strategic, and determinative, particularly in the building of the peace culture needed to ccelerate the national developmental programmes. Consequently, from the socio-political perspective, surely the development program is systemicly determined by factors of how far the religious tolerance or the peace culture is successfully carried out. This article endevours to analytically describe of how far the urgency of religious tolerance on behalf of strengtening the peace culture in our country. In his analysis, it is virtually highlighted that the religious tolerance plays very important roles that might be regarded as precondition for the successful development and NKRI (Unified state of Republic of Indonesia) empowerment. For gaining its effectivity, cultivating religious tolerance culture become pivotel to be intensively implemented in our country. KEYWORDS: Religious tolerance, peace culture, security, development, informal (family) education.